(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Mefenamic acid loaded chitosan microspheres were prepared both by thermal and gluteraldehyde cross linking methods and high level of entrapment of Mefenamic acid was obtained in gluteraldehyde cross linking method. The microspheres exhibited good swelling properties. DTA confirmed that Mefenamic acid was in solid dispersion in gluteraldehyde cross-linked chitosan microspheres. These microspheres exhibited faster release at low loading in comparison to high loading. Fitting the dissolution data of microspheres in Ritger-Peppas equation showed that at low loading the diffusional exponent (n) were high. As the polymer content increased the value of diffusional exponent approached to one, which is indicative of nearly zero order release.